Isolement et caractérisation technologiques des bactéries lactiques isoloées a partir de lait de chèvre et de vache - ABDELKRIM, Naziha (My University, 2022)
The pre-identification of bacteria necessarily involves observing the phenotypic and physio-chemical characteristics that lead to defining the genus. These analyzes must be supported by the search for a few technological characteristics. This work made it possible to process samples of raw milk from two sources (goat and cow) and focused mainly on the isolation of strains of mesophilic lactobacilli. Six strains were isolated. They have very interesting technological abilities such as antibacterial activity in terms of antagonism and the synthesis of EPS.
Keywords: Lactobacillus; exopolysaccharides EPS; antibacterial activity; Proteolyytic activity